2022
DOI: 10.1038/s41598-022-22171-7
|View full text |Cite
|
Sign up to set email alerts
|

Deep residual neural-network-based robot joint fault diagnosis method

Abstract: A data driven method-based robot joint fault diagnosis method using deep residual neural network (DRNN) is proposed, where Resnet-based fault diagnosis method is introduced. The proposed method mainly deals with kinds of fault types, such as gain error, offset error and malfunction for both sensors and actuators, respectively. First, a deep residual network fault diagnosis model is derived by stacking small convolution cores and increasing the core size. meanwhile, the gaussian white noise is injected into the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…The figure results provided by STM and the discussion of this review can provide a helpful impact on the future development of service robots. The results showed that increasing research is biased toward the application of intelligent algorithms [35,36,47,48,50,52]. The emergence of technologies such as neural networks and deep learning has improved the diagnostic efficiency and accuracy of service robots.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The figure results provided by STM and the discussion of this review can provide a helpful impact on the future development of service robots. The results showed that increasing research is biased toward the application of intelligent algorithms [35,36,47,48,50,52]. The emergence of technologies such as neural networks and deep learning has improved the diagnostic efficiency and accuracy of service robots.…”
Section: Discussionmentioning
confidence: 99%
“…Service robots are better adapted to complex environments and meet the essential work needs of human-machine collaborative interaction. Meanwhile, regional differences have brought new requirements to service robots' fault diagnosis, creating more unique service robots [35,76,80,81,87,92]. The main contributions of this review can be concluded as follows: (1).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, even if robots have the same specifications and perform identical tasks in the same space, the types and characteristics of faults may differ. Hence, ongoing research is primarily directed at diagnosing faults in rotating components like the driving module [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%